Tendon Cells Derived From The Long Head Of The Biceps And The Supraspinatus Tendons Of Patients Affected By Rotator Cuff Tears Show Different Expression Of Inflammatory Markers. (3rd September 2021) - Viganò, Marco; Lugano, Gaia; Orfei, Carlotta Perucca; Menon, Alessandra; Ragni, Enrico; Colombini, Alessandra; de Luca, Paola; Talò, Giuseppe; Randelli, Pietro S.; de Girolamo, Laura
ABSTRACT: Aim of the study: Tendons are exposed to mechanical stress constantly during movements and thus they are frequently subjected to injuries. Rotator cuff tears are common musculoskeletal disorders, mainly involving the supraspinatus tendon. The characterization of the tenocytes derived from this tendon and the comparison to cells isolated from the long head of the biceps tendon obtained from donors affected by rotator cuff disease may improve the knowledge of the cellular mechanisms involved in the initiation and progression of the pathology. Thus, the aim of the present study was to characterize and compare donor-matched human tendon cells (TCs) isolated from the long head of the biceps (LHB-TCs) and the supraspinatus tendons (SSP-TCs) of patients affected by rotator cuff tears. Methods: donor-matched LHB-TCs and SSP-TCs were isolated and cultured up to passage 3. Phenotypic appearance, metabolic activity, DNA content, production of soluble mediators (IL-1Ra, IL-1β, IL-6, and VEGF) and gene expression of tendon markers ( SCX, COL1A1, COL3A1 ), inflammatory ( PTGS2 ), and catabolic enzymes ( MMP-1, MMP-3 ) were evaluated. Results: LHB-TCs showed an elongated fibroblast-like shape, while SSP-TCs appeared irregular with jagged membrane. SSP-TCs gene expression revealed an augmented production of PTGS2, a marker of inflammation, whereas they produced a reduced amount of IL-6, in respect to LHB-TCs. Conclusion: SSP-TCs showed higher cellular stress and expression of inflammatory markers with respect to donor-matched LHB-TCs, suggesting that addressing the physio-pathological state of supraspinatus tendon cells during treatment of rotator cuff tears could favor tissue healing and possibly prevent relapses.